Medical-legal radiology. An ethical dilemma for radiology technician - Vicente-Ramírez, Rosa M.; Del Barrio Fernández, J. L.; Rodríguez Caravaca, G. (Acta Bioethica, 2017)
The medico-legal, radiological examinations include those medical exposures to radiation conducted by court order a person who is not sick. The radiologic technologist has a duty to minimize the dose to patients and the population as a whole, therefore, make this type of exploration conflicts with the maximum of Radiation Protection and its ethical code. We present a review study where we analyze whether these medical practices are contrary to professional ethics of the Radiologic technologist.